Association of Different Types of Diabetic Autonomic Neuropathy With Left Ventricular Diastolic Dysfunction in Patients With Type 2 Diabetes: A Cross‐Sectional Study - Ruixue Feng; Donge Yan; Mingxin Bai; Xingwu Ran; Dawei Chen; Chun Wang; Lihong Chen; Shuang Lin; Sen He; Yan Liu; Murong Wu; Zhiyi Lei; et al. (Journal of Diabetes)
ABSTRACT Background To investigate the association between different categories of diabetic autonomic neuropathy (DAN) and left ventricular diastolic dysfunction (LVDD) in patients with type 2 diabetes mellitus (T2DM). Methods We conducted a cross‐sectional study of 3440 participants with T2DM recruited in Diabetic Foot Care Center of West China Hospital, Sichuan University from January 2016 to February 2024. LVDD was assessed via echocardiography, defined as an average E/e′ ratio > 14. Twenty‐four hour Holter ECG, postvoid residual volume (PVR) examinations, and gastric emptying scintigraphy were employed to evaluate cardiac autonomic dysfunction, diabetic neurogenic bladder (DNB), and diabetic gastrointestinal autonomic neuropathy (DGAN), respectively. Logistic regression and propensity score matching (PSM) analyses were employed to examine the associations. Results Severe cardiac autonomic dysfunction (SDNN < 50 ms) was independently associated with LVDD, with odds ratios (OR) 1.731 (95% CI: 1.103–2.719, p = 0,018) after adjustment for potential confounding factors. LVDD tended to be independently associated with DNB (OR 1.356; 95% CI [0.992, 1.856]; p = 0.056). PSM analysis further validated the independent associations of SDNN < 50 ms (OR 1.587, 95% CI 1.028, 2.450, p = 0.037) and DNB (OR 1.454, 95% CI 1.011, 2.090, p = 0.043). However, DGAN was not independently associated with LVDD. Additionally, women had a higher risk of LVDD compared to men (OR 1.995, 95% CI 1.379, 2.885, p < 0.001). Conclusions Severe (SDNN < 50 ms), rather than mild–moderate, cardiac autonomic dysfunction, and DNB are independently associated with LVDD in individuals with T2DM. Additionally, women have a higher risk of LVDD than men.